2000
DOI: 10.1111/j.1529-8027.2000.22-58.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Streptozotocin‐induced Diabetes on Ngf, P75(ntr) and Trka Content of Prevertebral and Paravertebral Rat Sympathetic Ganglia

Abstract: Diabetic autonomic neuropathy results in significant morbidity and mortality. Both diabetic humans and experimental animals show neuroaxonal dystrophy of autonomic nerve terminals, particularly in the prevertebral superior mesenteric ganglia (SMG) and celiac ganglia (CG) which innervate the hyperplastic/hypertrophic diabetic small intestine. Previously, investigators suggested that disturbances in ganglionic nerve growth factor (NGF) content or transport might play a pathogenetic role in diabetic autonomic pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2003
2003
2003
2003

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Transgenic studies have shown that in development trk A receptor mediates neuronal survival by blocking apoptotic p75 signals (Majdan et al, 2001), emphasizing the importance of p75 interaction with trk neurotrophin receptors. Alternatively, it has been demonstrated that there is a reduction in expression of p75 in the autonomic ganglia of STZ-diabetic rats (Schmidt et al, 2000), reducing NGF signaling into the neurons. Regardless of mechanism, it is apparent that the low-affinity neurotrophin receptor is essential to the integrity of small nerve fibers involved in pain, warm thermal perception, and sweating and as such, constitute an important target for corrective therapy in diabetic neuropathy.…”
Section: Neurotrophin Receptorsmentioning
confidence: 99%
“…Transgenic studies have shown that in development trk A receptor mediates neuronal survival by blocking apoptotic p75 signals (Majdan et al, 2001), emphasizing the importance of p75 interaction with trk neurotrophin receptors. Alternatively, it has been demonstrated that there is a reduction in expression of p75 in the autonomic ganglia of STZ-diabetic rats (Schmidt et al, 2000), reducing NGF signaling into the neurons. Regardless of mechanism, it is apparent that the low-affinity neurotrophin receptor is essential to the integrity of small nerve fibers involved in pain, warm thermal perception, and sweating and as such, constitute an important target for corrective therapy in diabetic neuropathy.…”
Section: Neurotrophin Receptorsmentioning
confidence: 99%